2014
DOI: 10.3390/ijms150813424
|View full text |Cite
|
Sign up to set email alerts
|

The Constituents of Roots and Stems of Illigera luzonensis and Their Anti-Platelet Aggregation Effects

Abstract: Phytochemical investigation of the roots and stems of Illigera luzonensis afforded two new aporphine alkaloids (1) and (2), one new bisdehydroaporphine alkaloid (3), and one new benzenoid (4), along with 28 known structures. The structures of new compounds were elucidated by spectral and MS analysis. Among the isolated compounds, (1) and (4–13) were subjected into the examination for their inhibitory effects on the aggregation of washed rabbit platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Each layer was subjected to purification by a combination of conventional chromatographic techniques to result in one new compound ( 1 ). In addition, thirty-two known compounds were identified to be 5,7-dimethoxycoumarin ( 2 ) [ 3 ], xanthyletin ( 3 ) [ 18 ], oxypeucedanin hydrate ( 4 ) [ 35 ], 6,7-dimethoxycoumarin ( 5 ) [ 18 ], skimmin ( 6 ) [ 36 ], haploperoside A ( 7 ) [ 37 ], leptodactylone ( 8 ) [ 18 ], 7-methoxycoumarin ( 9 ) [ 18 ], scopoletin ( 10 ) [ 36 ], cis -head-to-tail-limittin dimer ( 11 ) [ 38 ], umbelliferone ( 12 ) [ 36 ], nordentatin ( 13 ) [ 18 ], limonin ( 14 ) [ 18 ], nomilin ( 15 ) [ 18 ], citrusin ( 16 ) [ 3 ], obacunone ( 17 ) [ 39 ], 3-(2- O -β- d -glucopyranosyl-4-methoxyphenyl)-propanoic acid ( 18 ) [ 40 ], cis - p -coumaric acid ( 19 ) [ 18 ], methyl vanillate ( 20 ) [ 41 ], methyl benzoate ( 21 ) [ 42 ], methyl paraben ( 22 ) [ 43 ], 4-hydroxy-phenethyl alcohol ( 23 ) [ 44 ], methyl-4-hydroxycinnamate ( 24 ) [ 43 ], coniferin ( 25 ) [ 45 ], syringin ( 26 ) [ 45 ], ( E )-6-hydroxy-2,6-dimethylocta-2,7-dienoic acid ( 27 ) [ 46 ], a mixture of stigmasterol ( 28 ) [ 3 ] and β-sitosterol ( 29 ) [ 3 ], β-sitosteryl glucoside ( 30 ) [ 47 ], chrysoeriol 8- C -glucoside ( 31 ) [ 48 ], 1,2,3,4-tetrahydro-β-carboline-3-carboxylic acid ( 32 ) [ 49 ], and citrylidene malonic acid ( 33 ) […”
Section: Resultsmentioning
confidence: 99%
“…Each layer was subjected to purification by a combination of conventional chromatographic techniques to result in one new compound ( 1 ). In addition, thirty-two known compounds were identified to be 5,7-dimethoxycoumarin ( 2 ) [ 3 ], xanthyletin ( 3 ) [ 18 ], oxypeucedanin hydrate ( 4 ) [ 35 ], 6,7-dimethoxycoumarin ( 5 ) [ 18 ], skimmin ( 6 ) [ 36 ], haploperoside A ( 7 ) [ 37 ], leptodactylone ( 8 ) [ 18 ], 7-methoxycoumarin ( 9 ) [ 18 ], scopoletin ( 10 ) [ 36 ], cis -head-to-tail-limittin dimer ( 11 ) [ 38 ], umbelliferone ( 12 ) [ 36 ], nordentatin ( 13 ) [ 18 ], limonin ( 14 ) [ 18 ], nomilin ( 15 ) [ 18 ], citrusin ( 16 ) [ 3 ], obacunone ( 17 ) [ 39 ], 3-(2- O -β- d -glucopyranosyl-4-methoxyphenyl)-propanoic acid ( 18 ) [ 40 ], cis - p -coumaric acid ( 19 ) [ 18 ], methyl vanillate ( 20 ) [ 41 ], methyl benzoate ( 21 ) [ 42 ], methyl paraben ( 22 ) [ 43 ], 4-hydroxy-phenethyl alcohol ( 23 ) [ 44 ], methyl-4-hydroxycinnamate ( 24 ) [ 43 ], coniferin ( 25 ) [ 45 ], syringin ( 26 ) [ 45 ], ( E )-6-hydroxy-2,6-dimethylocta-2,7-dienoic acid ( 27 ) [ 46 ], a mixture of stigmasterol ( 28 ) [ 3 ] and β-sitosterol ( 29 ) [ 3 ], β-sitosteryl glucoside ( 30 ) [ 47 ], chrysoeriol 8- C -glucoside ( 31 ) [ 48 ], 1,2,3,4-tetrahydro-β-carboline-3-carboxylic acid ( 32 ) [ 49 ], and citrylidene malonic acid ( 33 ) […”
Section: Resultsmentioning
confidence: 99%
“…Moreover, curcumin was the most effective antiplatelet compound as it inhibited arachidonic acid, collagen, and ADP-induced platelet aggregation with IC 50 values of 37.5, 60.9, and 45.7 μM, respectively (Jantan et al, 2008 ). Similarly, Huang et al ( 2014 ) reported that aporphine alkaloids are the primary components of Illigeralu zonensis , exhibited varying degrees of antiplatelet activity effect. However, bisdehydroaporphine and actinodaphnine were most potent alkaloids (Huang et al, 2014 ).…”
Section: Alkaloids As Antiplatelet Agentsmentioning
confidence: 92%
“…Similarly, Huang et al ( 2014 ) reported that aporphine alkaloids are the primary components of Illigeralu zonensis , exhibited varying degrees of antiplatelet activity effect. However, bisdehydroaporphine and actinodaphnine were most potent alkaloids (Huang et al, 2014 ). Furthermore, a study carried out by Wu et al ( 2003 ) on Rutagra graveolens , a plant belonging to family Rutaceae revealed the presence of dictamine, chalepensin, clausindin, and graveolinine; these compounds displayed significant inhibition of platelet aggregation (Wu et al, 2003 ).…”
Section: Alkaloids As Antiplatelet Agentsmentioning
confidence: 92%
See 2 more Smart Citations